2011
DOI: 10.1038/nsmb.2016
|View full text |Cite
|
Sign up to set email alerts
|

Genetic selection designed to stabilize proteins uncovers a chaperone called Spy

Abstract: To optimize the in vivo folding of proteins, we linked protein stability to antibiotic resistance, thereby forcing bacteria to effectively fold and stabilize proteins. When we challenged Escherichia coli to stabilize a very unstable periplasmic protein, it massively overproduced a periplasmic protein called Spy, which increases the steady-state levels of a set of unstable protein mutants up to 700-fold. In vitro studies demonstrate that the Spy protein is an effective ATP-independent chaperone that suppresses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
218
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(230 citation statements)
references
References 45 publications
(65 reference statements)
7
218
0
2
Order By: Relevance
“…Among the genes regulated by this system are those specifying multidrug efflux pump components (mdtABCD and acrD) and the periplasmic chaperone spy (50). Previously isolated baeS alleles, which dramatically upregulate the production of Spy, mapped to nearby amino acids (E264 and D268) (42). It has also been shown that Spy can protect substrate proteins from aggregation in vitro and that overexpression of Spy can stabilize an unstable variant of the colicin E7 immunity protein (Im7) in vivo (42).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the genes regulated by this system are those specifying multidrug efflux pump components (mdtABCD and acrD) and the periplasmic chaperone spy (50). Previously isolated baeS alleles, which dramatically upregulate the production of Spy, mapped to nearby amino acids (E264 and D268) (42). It has also been shown that Spy can protect substrate proteins from aggregation in vitro and that overexpression of Spy can stabilize an unstable variant of the colicin E7 immunity protein (Im7) in vivo (42).…”
Section: Resultsmentioning
confidence: 99%
“…Construction of the psurA plasmid (pAER1) has been previously described (14). The pspy plasmid was reconstructed as previously described (42).…”
Section: Methodsmentioning
confidence: 99%
“…We have extensively utilized Im7 as a test protein because of the ready availability of mutants with well-defined levels of stability and the well-studied nature of Im7's folding pathway [18]. We have previously shown that very unstable mutants of the test protein Im7, when inserted into our stability biosensors, show an up to 4 fold enhancement β-lactamase levels upon overproduction of the periplasmic chaperone Spy [19]. More stable mutants of Im7 and wild type Im7 show smaller or insignificant fold increases in β-lactamase levels upon the overproduction of this chaperone (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…In column 1, protein folding in vitro is limited to the chemical information contained in the polypeptide chain sequence and is strongly influenced by the choice of the folding buffer. In the simplest case in vivo, illustrated by column 2 (such as found in extant Bacteria and Archaea), one cytosolic PN (the orange cloud) manages all intracellular folding and the export of proteins to and through the cell surface, although specialized chaperones can manage folding in the environment immediately outside the cell (Evans et al 2011;Powers and Balch 2011;Quan et al 2011). The small gray cloud icon surrounding the protein (dark circle) defines the select PN components used by a particular protein to facilitate its own structure/function relationships.…”
Section: Trafficking Biology As An Arm Of Proteostasis Biologymentioning
confidence: 99%